Children road safety awareness: Design and development of a road safety application - Shaari, Nassiriah; Saidin, Aeni Zuhana; Alwi, Asmidah (UTM Press, 2015)
Road safety campaigns and programs have been extensively introduced and implemented in Malaysia. However, their effectiveness is still being debated. Children especially will become the unfortunate victims of road accidents if they are unaware of the danger and precaution actions to be safe on the road. In response to that, this paper introduces an application as an alternative that inculcates road safety awareness to further support existing related programs and campaigns. Particularly, an interactive web application incorporating interactive multimedia elements has been designed and evaluated. Results on the usability test indicate a promising success and highlight aspects and issues that can be further focused for improvement and enhancement.